The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1063/1.3655329
|View full text |Cite
|
Sign up to set email alerts
|

The role of a diffusion barrier in plasma display panel with the high gamma cathode layer

Abstract: Plasma display panel (PDP) with MgO-SrO double cathode layer and SiO 2 diffusion barrier is proposed to make the SrO layer free of contaminations. Time of flight-secondary ion mass spectrometry (TOF-SIMS) analysis shows the diffusion of impurities, like Na and K, can be effectively blocked while a new SrO layer is formed on top of the MgO layer. This structure shows that high Xe gases can be used to improve the luminous efficacy 2.3 times and decrease the voltage margin more than 10 V compared to the conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…[43] Studies on thin films have also shown that SrO layer forms on top of MgO due to Sr out diffusion. [44] It is therefore likely that Sr out diffuses faster than the other species and exhibits enhanced oxidizing on the top surface.…”
Section: Sr Diffusivity May Be Higher Than That Of Mg and O Transportmentioning
confidence: 99%
“…[43] Studies on thin films have also shown that SrO layer forms on top of MgO due to Sr out diffusion. [44] It is therefore likely that Sr out diffuses faster than the other species and exhibits enhanced oxidizing on the top surface.…”
Section: Sr Diffusivity May Be Higher Than That Of Mg and O Transportmentioning
confidence: 99%